Surface roughness optimization in end milling of stainless steel AISI 304 with uncoated WC-Co insert under magnetic field - Amin, A. K. M. Nurul; Sulaiman, Syidatul Akma; Mohd Zainun, Siti Noor Izzati; Arif, Muammer Din (Trans Tech Publications, Switzerland, 2012)
Chatter phenomenon is a major issue as it greatly affects the topography of machined parts. Due to the inconsistent character of chatter, it is extremely difficult to predict resultant surface roughness in a machining process, such as end milling. Also, recent studies have shown that chatter can be suitably damped using magnetic fields. This paper, thus, focuses on a novel approach of minimizing surface roughness in end milling of Mild (Low Carbon) Steel using uncoated WC-Co inserts under magnetic field from permanent magnets. In this experiment, Response Surface Methodology (RSM) approach using DESIGN EXPERT 6.0 (DOE) software was used to design the experiments. The experiments were performed under two different cutting conditions. The first one was cutting under normal conditions, while the other was cutting under the application of magnetic fields from two permanent magnets positioned on opposite sides of the cutter. Surface roughness was measured using Mitutoyo SURFTEST SV-500 profilometer. The subsequent analysis showed that surface roughness was significantly reduced (by as much as 67.21%) when machining was done under the influence of magnetic field. The experimental results were then used to develop a second order empirical mathematical model equation for surface roughness and validated to 95% confidence level by using ANOVA. Finally, desirability function approach was used to optimize the surface roughness within the limiting values attainable in end milling.